Safety and tolerability of oral lisdexamfetamine in adults with methamphetamine dependence: a phase-2 dose-escalation study - Ezard, Nadine (BMJ Open, 2021)
OBJECTIVES: To examine the safety of an agonist-type treatment, lisdexamfetamine (LDX), at 250 mg/day among adults with methamphetamine (MA) dependence. DESIGN: A dose-escalating, phase-2, open-label, single-group study of oral LDX at two Australian drug treatment services. SETTING: The study was conducted at two Australian stimulant use disorder treatment clinics. PARTICIPANTS: There were 16 participants: at least 18 years old, MA dependent for at least the preceding 2 years using ICD-10 criteria, reporting use of MA on at least 14 of the preceding 28 days. INTERVENTIONS: Daily, supervised LDX of 100–250 mg, single-blinded to dose, ascending-descending regimen over 8 weeks (100–250 mg over 4 weeks; followed by 4-week dose reduction regimen, 250–100 mg). Participants were followed through to week 12. OUTCOMES: Primary outcomes were safety, drug tolerability and regimen completion at the end of week 4. Participants were followed to week 12. Secondary outcomes included: change in MA use; craving; withdrawal; severity of dependence; risk behaviour; change in other substance use; medication acceptability; potential for non-prescription use; adherence and neurocognitive functioning. RESULTS: Fourteen of 16 participants (87.5%) completed escalation to 250 mg/day. Two participants withdrew from the trial in the first week: one relocated away from the study site, the other self-withdrew due to a possible, known side effect of LDX (agitation). There was one serious adverse event of suicidal ideation which resolved. All other adverse events were mild or moderate in severity and known side effects of LDX. No participant was withdrawn due to adverse events. MA use decreased from a median of 21 days (IQR: 16–23) to 13 days (IQR: 11–17) over the 4-week escalation period (p=0.013). CONCLUSIONS: LDX at a dose of up to 250 mg/day was safe and well tolerated by study participants, warranting larger trials as a pharmacotherapy for MA dependence. TRIAL REGISTRATION NUMBER: ACTRN12615000391572.